A History of the Faculty of Arts at the University of Adelaide 1876-2012 - Harvey, Nick; Fornasiero, Jean; McCarthy, Greg; Macintyre, Clem; Crossin, Carl (University of Adelaide Press, 2012)
The Bachelor of Arts (BA) was the first recognised degree at the University of Adelaide. Although informal classes for some subjects were held at the University between 1873 and 1875, the first official University lecture was a Latin lecture at 10 am on Monday 28 March 1876. This was followed by lectures in Greek, English and Mental Philosophy. By 1878, the first BA student, Thomas Ainslie Caterer, completed his studies for the BA degree and in 1879 became the first graduate of the University of Adelaide. [...] In the first 50 years of the University's existence, less than ten BA students graduated each year. At the start of the 21st century this figure had climbed to over 300 BA graduates per year but what is interesting is that by 2010 the number of BA graduates was equalled by the number of graduates from separate named degrees within the Faculty plus 70 Music graduates.